2021
DOI: 10.3390/antibiotics10050535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunological Profiles of SARS-CoV-2 Variants in the COVID-19 Pandemic Trends: An Immunoinformatics Approach

Abstract: The current dynamics of the COVID-19 pandemic have become a serious concern with the emergence of a series of mutant variants of the SARS-CoV-2 virus. Unlike the previous strain, it is reported that the descendants are associated with increased risk of transmission yet causing less impact in terms of hospital admission, the severity of illness, or mortality. Moreover, the vaccine efficacy is also not believed to vary among the population depending on the variants of the virus and ethnicity. It has been determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Thereby, it is plausible to assume that these epitopes could be responsible for the strong activation of the cell-mediated immune response ( Patronov et al, 2011 ; Sarma, Olotu & Soliman, 2021 ) in case of an experimental assay. In addition, the RBD epitopes have a broad populational coverage consistent with studies for SARS-CoV-2 epitopes identified in lineages isolated from India, England and the United States ( Mallavarpu Ambrose et al, 2021 ). These findings combined with the high conservancy, antigenicity and immunogenicity suggest these epitopes’ in silico immunogen profile ( Zheng & Song, 2020 ; Mallavarpu Ambrose et al, 2021 ; Jahangirian et al, 2021 ), validating the accurate selection of EpiCurator.…”
Section: Discussionsupporting
confidence: 70%
“…Thereby, it is plausible to assume that these epitopes could be responsible for the strong activation of the cell-mediated immune response ( Patronov et al, 2011 ; Sarma, Olotu & Soliman, 2021 ) in case of an experimental assay. In addition, the RBD epitopes have a broad populational coverage consistent with studies for SARS-CoV-2 epitopes identified in lineages isolated from India, England and the United States ( Mallavarpu Ambrose et al, 2021 ). These findings combined with the high conservancy, antigenicity and immunogenicity suggest these epitopes’ in silico immunogen profile ( Zheng & Song, 2020 ; Mallavarpu Ambrose et al, 2021 ; Jahangirian et al, 2021 ), validating the accurate selection of EpiCurator.…”
Section: Discussionsupporting
confidence: 70%
“…On this subject, the individual (epi)genetic make-up was investigated looking for specific variants and genes able to contribute to the susceptibility and progression to severe forms of COVID-19 [36]. In particular, an interesting role of immune genes (such as the HLA make-up) in the differential activation of host immune responses by SARS-CoV-2 variants was investigated, pointing out the importance of specific virus-host molecular interactions [37]. Therefore, studies at (epi)genome-wide level will certainly help to characterize groups of individuals with the same pattern of viral kinetics, providing useful insights for a more tailored and effective management of infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The promising epitope YQPYRVVVL has been reported to exhibit high antigenicity against the beta variant from South Africa (GSAID ID: EPI_ISL_1706561) and another variant from India (GSAID ID: EPI_ISL_1708422) [ 53 ]. Furthermore, this peptide exhibited high binding affinity for several HLAs in silico and has been proposed as candidate epitope for vaccine design [ 54 ].…”
Section: Discussionmentioning
confidence: 99%